Review of gynecologic and reproductive care for women with developmental disabilities. Issue 5 (October 2016) - Abells, Dara; Kirkham, Yolanda A.; Ornstein, Melanie P.
Abstract : Purpose of review: Care for women with developmental disabilities requires special consideration for unique needs related to their cognitive and physical abilities. These women and their caregivers require more support and guidance during reproductive health care. We review the literature and provide expert opinion surrounding gynecological issues for women with developmental disabilities to support healthcare providers better understand and care for this population. Recent findings: Women with developmental disabilities are more vulnerable to abuse and experience poorer gynecological healthcare outcomes. Many women with developmental disabilities are fertile and participate in sexual activity without adequate knowledge. They are at higher risk of pregnancy and birth complications. They are less likely to receive appropriate preventive screening. Summary: The review highlights important issues and practice suggestions related to the reproductive health care of women with developmental disabilities. Topics include clinic visits, menstruation, sexuality, sexual abuse, sexual health education, contraception, sexually transmitted infections, pregnancy, labor and delivery, and cancer screening/prevention. We emphasize the need for an individualized, comprehensive approach for these patients and review perceived and actual barriers to care. More education is needed on the aforementioned topics for women with developmental disabilities, their caregivers, and their providers.